Toward a Definition of International Literary Journalism - Bak, John S. (Brazilian journalism research, 2017)
At the end of the nineteenth century, several countries were developing journalistic traditions similar to what we identify today as literary journalism or literary reportage. Throughout most of the twentieth century, however, and in particular after World War I, that tradition was overshadowed and even marginalized by the general perception among democratic states that journalism ought to be either “objective,” as in the American tradition, or “polemical,” as in the European one. Nonetheless, literary journalism would survive and at times even thrive. How and why is a story unique to each nation. The aim of this essay, a revised and updated version of the introduction published in the book Literary Journalism across the Globe: Journalistic Traditions and Transnational Influences, co-edited with Bill Reynolds (Amherst and Boston: University of Massachusetts Press, 2011), is to assess the extent to which literary journalism over the past century has influenced reporting in various nations—some of which have only recently known democracy, while others are still under full or partial state control—and how it might shape journalistic heuristics and literary aesthetics in the twenty-first century. No final do século XIX, vários países estavam desenvolvendo tradições jornalísticas ao que identificamos atualmente como Jornalismo Literário ou reportagem literária. Contudo, ao longo da maior parte do século XX, e particularmente após a Primeira Guerra Mundial, essa tradição foi ofuscada e até mesmo marginalizada pela percepção geral entre os estados democráticos de que o jornalismo deveria ser ou “objetivo”, como na tradição estadunidense, ou “polêmico”, como na tradição europeia. No entanto, o Jornalismo Literário iria sobreviver e, às vezes, até mesmo prosperar. Como e por que é uma narrativa única para cada nação. Almejamos nesse ensaio, que se trata da introdução revista e atualizada publicada no livro Literary Journalism across the Globe: Journalistic Traditions and Transnational Influences, coeditado com Bill Reynolds (Amherst and Boston: University of Massachusetts Press, 2011), avaliar até que ponto o Jornalismo Literário, ao longo do século passado, influenciou as reportagens em várias nações – algumas das quais só conheceram a democracia recentemente, enquanto outras ainda estão parcial ou totalmente sob controle estatal – e como ele poderia moldar a heurística jornalística e a estética literária no século XXI. Palavras-chave: Jornalismo. Jornalismo Literário internacional. Reportagem. Verdade versus fato. Imprensa democrática. A finales del siglo XIX, en diversos países se estaba desarrollando en sus tradiciones periodísticas un fenómeno similar a lo que hoy conocemos como periodismo literario o reportaje literario. Sin embargo, durante la mayor parte del siglo XX, y en particular después de la Primera Guerra Mundial, esa tradición fue eclipsada e incluso marginada por la percepción general entre los estados democráticos de que el periodismo debía ser “objetivo,” como en la tradición americana, o polémico, como en la europea. Sin embargo, el periodismo literario sobrevivió y con el tiempo incluso prosperó. El cómo y el por qué es un caso único de cada nación. El propósito de este ensayo, que se trata de la introducción revisada y actualizada publicada en el libro Literary Journalism a través del Globo: periodística de tradiciones y transnacionales influencias, coeditado con Bill Reynolds (Amherst and Boston: University of Massachusetts Press, 2011), evaluar hasta qué punto el periodismo literario durante el siglo pasado ha influido reportando lo que ocurría en diversos países—algunos de los cuales han conocido recientemente la democracia, mientras que otros están bajo el control total o parcial del estado—y cómo ha podido dar forma a la heurística periodística y la estética literaria en el siglo XXI.